Refined crude glycerin in sow feed: A sustainable alternative - de la Torre Iturbe, Sandra; Sánchez Cantú, Manuel; Méndez Mendoza, Maximino; Cansino Alonso, Iyoselin (Acta Scientiarum. Animal Sciences, 2025)
The objective of this work was to evaluate the effect of semi-purified glycerin added to the feed of pregnant and lactating sows on performance including dorsal diameter, body condition, daily weight gain, feed intake, and feed conversion rate. Growth and feeding parameters were evaluated in born piglets: litter average, survival, daily weight gain, feed conversion rate, and daily milk consumption. Pregnant sows (n = 60; initial weight 180 ± 22 kg) were randomly assigned to the Control or Glycerin group (2%). Semi-purified glycerin was supplied from the beginning of gestation until farrowing. The inclusion of semi-purified glycerin did not affect any of the parameters evaluated in sows during gestation. The inclusion of semi-purified glycerin had a significant effect (p = 0.04) on the body condition of sows at weaning and appeared to have a negative effect on piglet survival. However, semi-purified glycerin caused no negative effects on milk production during lactation and did not affect piglet performance parameters. The addition of semi-purified glycerin as a caloric source could be an economically viable alternative to be implemented in feeding pregnant and lactating sows. However, additional tests are suggested.